If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(4x + -4) = 3(12x + 3) Reorder the terms: 9(-4 + 4x) = 3(12x + 3) (-4 * 9 + 4x * 9) = 3(12x + 3) (-36 + 36x) = 3(12x + 3) Reorder the terms: -36 + 36x = 3(3 + 12x) -36 + 36x = (3 * 3 + 12x * 3) -36 + 36x = (9 + 36x) Add '-36x' to each side of the equation. -36 + 36x + -36x = 9 + 36x + -36x Combine like terms: 36x + -36x = 0 -36 + 0 = 9 + 36x + -36x -36 = 9 + 36x + -36x Combine like terms: 36x + -36x = 0 -36 = 9 + 0 -36 = 9 Solving -36 = 9 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 9x^2-5+2x-3x^2-13= | | -7x=27 | | -1.3a=-10.4 | | 234=10x | | 4(3v+3)+v= | | 27t^3-64x^6=0 | | 234=10+x | | x-2=x+24 | | -4u+3+u-4= | | p^3+512=0 | | m^3-8=0 | | s=p-12 | | 11y-17=8y+1 | | -2(4u-y)-2(-3y+u)= | | -(4y+1)-(-3y-5)=3 | | 4x^4+2x^3+x^2=0 | | 4(v+1)-7=3(v-1)+v | | x-38=-36 | | 8+4y-5=7y+10-2y | | 8=-6x-4 | | 18x^2-48xy+32y^2=0 | | 8x+9x=153 | | -9.7=4.7+y | | 36y^2-60y+25=0 | | -9(3b+2)+(28b-4)=0 | | 3.1q-2.2-3.7q=-1.6q-1.6 | | -(-v+x)+2(-4x-5v)= | | n-35=-44 | | 8-8y=2y+7878 | | -(8y+2)-(-7y-7)=2 | | 3(n-2)-1=2-5(n+5) | | 52=(4x+1)(x+1) |